Ethics in Medical Practice and Research - Kattel, Pramod (Journal of Advances in Internal Medicine, 2021)
Ethics is a moral guide that helps the treatment group to be treated with due respect and care following the standard of practice. It also helps the research to be conducted without or minimal harm to the population under study. Besides ethics, clinical practice and research are guided by some nationally and internationally accepted principles or codes of conduct. The human subject under treatment or study should be respected to the utmost level and should be performed by trained personnel. The importance of ethics starts before studies so should be kept in medical curricula starting from basic sciences so that medical practitioners become acquainted from the beginning of the study.